Surface modification of nanocontainers of corrosion inhibitors for improved compatibility with protective polymer coatings - Carneiro, Jorge Augusto Oliveira (2019)
The application of organic coatings is one of the most widely used preventive measures to protect metal alloys against corrosion. Typically, anti-corrosion coatings combine passive and active protection, the former being based upon barrier effect of the matrix against ingress of active species and the later due to the presence of corrosion inhibitors directly dispersed in the coating matrix. Nevertheless, the direct addition of corrosion inhibitors to coating formulations often leads to detrimental effects, thus impairing the overall coating performance. To circumvent this limitation, micro and nanocontainers as hosting structures for storage and controlled release of corrosion inhibitors, have been proposed. If this release is triggered by adverse conditions that result in corrosion initiation self-healing takes place, which can bring great benefit to high-performance applications. The work presented in this thesis aims at modifying the nanocontainers surface in order to enhance the role of inhibition and barrier properties of the coatings as well as improving their dispersibility and compatibility within the coating. This latter part of the study had not been in general addressed in the scientific literature and requires interaction with the coating producer in order to match the desired properties for a commercial formulation. Two nanocontainers to store the corrosion inhibitors were selected: layered double hydroxides (LDH) and silica nanocapsules (Si_NC). The surface modification of LDH loaded with 2-mercaptobenzothiazole (2-MBT) with poly(styrene sulfonate)/poly(allylamine hydrochloride) by the layer-by-layer self-assembly technique allowed the incorporation of a second corrosion inhibitor, cerium nitrate, but at the same time improve the coating barrier properties of the hybrid sol-gel coatings. Moreover, the release profile of 2-MBT was also changed with this surface modification. This lab-scale work was extended to an industrial collaboration with a steel producer. In this case, the modification of gluconate loaded LDH with alginate lead to improvement in coating barrier properties of a polyamide-based coating. In the case of Si_NC several functional groups were grafted onto these silica-based nanomaterials, allowing a thorough analysis of the effect the surface chemistry on the dispersibility and compatibility with coatings. Tests were carried out in systems with increasing complexity from solvents, to hybrid sol-gel formulations and water- and solvent-based coating formulations industrially available. The coating barrier properties were mainly assessed by electrochemical impedance spectroscopy, often complemented with other electrochemical methods. Spectroscopic and surface-characterization techniques, and in some cases standard tests carried out under an industrial environment were also used. The results prove the importance that the surface modification has on the nanocontainer dispersibility and in the nanocontainer/coating compatibility. These results obtained show that surface modification of these nanocontainers can tune the interaction with coating matrix, opening prospects for the industrialization of these controlled-release technologies in the area of protective coatings.